TRANSFORMING HALAL BUSINESS MANAGEMENT THROUGH DIGITAL INNOVATION AND SPIRITUAL ENTREPRENEURSHIP - Muhammad Umar Maya Putra; Zuhrinal M Nawawi; Muhammad Ramadhan (RADJA PUBLIKA, 2025)
Halal business management (HBM) today transcends the boundaries of mere Shariah compliance, evolving into an ethical, innovative, and sustainability-driven framework. This study explores the transformation of HBM through the integration of digital technologies such as block chain, big data, and sustainable finance—that enhance traceability, accountability, and consumer protection. Employing a descriptive qualitative approach, the research synthesizes theoretical and empirical insights to demonstrate how technological advancement harmonizes with Islamic ethical principles of justice (‘adl), trustworthiness (amanah), and excellence (iḥsān). Moreover, Islamic leadership and Islamic Spiritual Entrepreneurship (ISE) emerge as pivotal in embedding spiritual values, including barakah (divine blessing) and maṣlaḥah (social benefit), into business governance. Findings indicate that the synergy between HBM and ISE produces a holistic model of ethical innovation, ensuring that economic growth aligns with spiritual consciousness and social justice. Ultimately, the study affirms that integrating Shariah ethics, digital innovation, and spiritual entrepreneurship is key to constructing a just, sustainable, and globally competitive halal economic civilization